Desenvolvimento e validação de um instrumento para avaliação do conhecimento tático processual no basquetebol - Juan Carlos Pérez Morales (2014)
The objective of this study was to develop and validate an instrument to assess the procedural tactical knowledge in basketball (TCTP:Bb), in situation of three against three (3x3), in official basketball court, half court ("A" protocol) and whole court ("B" protocol). The study included 161 male basketball players, from 12 to 19 years old. The coefficient of content validity (CVC) was calculated for the clarity of language, practical relevance and theoretical relevance. The theoretical dimension of the instrument was established by calculating the Cohen's Kappa coefficient. Exploratory factor analysis of principal components and varimax orthogonal rotation with Kaiser normalization were conducted, in order to identify evidence of construct validity. Intra and inter observer reliability were investigated, by calculating the Cohen's Kappa coefficient. As regards the validity of the content, the instrument has reached a CVC of 0.94 for clarity of language, 0.96 for practical relevance and 0.95 for the theoretical significance. The value of Cohen's Kappa coefficient for theoretical dimension confirmed good or nearly perfect agreement among the judges for the dimensions attack and defense, as well as the subcategories of individual actions in the attack, defending individual actions, group actions in attack and actions group on defense. The four factor models or final solutions generated presented good fit and comply with the recommendations of the literature, with regard to the calculated values of Kaiser - Meyer - Olkim test (> 0.50), Bartlett's test (p 0.05), correlation matrix (loads greater than 0.30 and less than 0.90), measure of sampling adequacy (> 0.50), percentage of explained variance (> 60 %), communality (> 0.50), factor loads (> 0.51) and percentage of reproduced correlations (< 50%). The coefficient of Cohen's Kappa for the items/criteria validated by exploratory factor analysis presented, for "A" and "B" protocols, substantial and almost perfect agreement for items/criteria 1, 4, 5 and 6. The items/criteria 10, 11, 12, 13 and 14 showed reasonable and moderate agreement. The items/criteria 18, 19, 20 and 23 had moderate, substantial and almost perfect agreement. Finally, the items/criteria 25, 31, 30 and 32 showed reasonable and moderate agreement. The TCTP:Bb is a valid and reliable instrument to assess the procedural tactical knowledge in a situation of numerical equality (3x3) in half and whole basketball court.